EFL Teachers’ Lived Experiences in Teaching English to Young Learners - Rizka Pebriantini; Vianty, Machdalena; Amrullah (Universitas Hamzanwadi, 2024)
Teachers' lived experiences significantly shape their teaching approaches, particularly in Teaching English to Young Learners (TEYL), where understanding these experiences is essential for improving instructional practices. This qualitative phenomenological study explored EFL teachers' challenges in TEYL and their strategies to overcome them in elementary schools in Palembang. Data were collected through interviews and classroom observations with teachers with at least five years of experience in these school settings. The findings revealed three primary challenges: difficulties in managing classroom activities, the unique learning characteristics of young learners, and the use of Indonesian language during English lessons. To address these challenges, teachers employed strategies such as incorporating games into lessons, fostering a creative and engaging learning environment, encouraging consistent English usage by students, and consulting resources on young learners' language acquisition. The study underscores the importance of flexible, adaptive strategies in overcoming challenges in TEYL, highlighting how a better understanding of young learners' needs can improve the effectiveness of English teaching.